President’s Message - Farid, Donna (Operating Room Nurses Association of Canada Journal, 1998)
As President of the Operating Room Nurses Association of Canada (ORNAC), I report to the Canadian Nurses‘ Association in Ottawa on our association's aims and objectives, and our activities and accomplishments over the past year.